IMPROVING THE PROCESS AND OUTCOMES OF INDONESIAN LANGUAGE LEARNING USING THE THINK TALK WRITE MODEL - Anjilina, Anggun; Aprizan, Aprizan; Agrita, Tri Wera (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The objectives of this study are:To improve the Indonesian language learning process using the Think Talk Write model in Grade IV of SDN 36/II Sarana Jaya. To improve the learning outcomes in Indonesian using the Think Talk Write model in Grade IV of SDN 36/II Sarana Jaya. This study employed Classroom Action Research (CAR) as its method. The research was conducted in Grade IV of SDN 36/II Sarana Jaya, Bathin III District, Bungo Regency, during the even semester of the 2024/2025 academic year. The research subjects were 20 Grade IV students (12 girls and 8 boys) in the Indonesian language subject.Data collection techniques included observation, interviews, and documentation. Data analysis techniques involved analysis of observation data and student learning outcomes.The research findings on the teacher’s teaching process showed that at the end of Cycle I, the teacher's activity was categorized as good/active with a percentage of 75%, and in Cycle II, it improved to very good/active with a percentage of 95%. Regarding the student learning process, Cycle I showed an increase from 40% to 65%, and Cycle II further improved from 75% to 90%. It can be concluded that the student learning process improved in each cycle. As for student learning outcomes in Indonesian, in Cycle I the achievement rate was 70%, categorized as